PERANCANGAN RUTE FORKLIFT TRUCKS UNTUK MEMINIMASI WAKTU PERJALANAN - Nurlailah Badariah; Docki Saraswati; Astari Putri Dwityaningsih (Jurusan Teknik Industri, Fakultas Teknologi Indusri Universitas Trisakti, 2015)
The purpose of this study is to minimize the travel time of forklift trucks. Currently thetotal travel time for the nine locations that using forklift trucks is 41.39 minute, and the averagetime for activities in each site is constant 90.15 minutes. The main problem shown by the researchis that the travel time has not reached the optimal time. The result from random sampling methodis 38.17 minutes. The solution reached from Genetic Algorithm is 34.80 minutes as the route fromMaintenance Cutting Logistic Gas Metering Regulating Station Fabrication Transformer Tank Fabrication General Fabrication Stamping Products WarehouseMaterial Warehouse and back to Maintenance with 16% of decreased travel time from priorcondition optimized by Genetic Algorithm.